Correlations Between Learning Strategy And The Ninth Grade Students’ Reading Comprehension Of State Junior High School 01 Buayrawan Oku Selatan - Candrawati, Marini; Simaibang, Baginda; Mulyadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study is limited to the investigation of the correlation between students’ learning strategy, and reading comprehensionof the ninth grade students at State Junior High School 01 Buay Rawan, OKU Selatan. There were 85 students who has been selected as the sample of the research. The writer used correlational study and formula to see the correlation between two variable stated. Correlation about Students’ Learning Strategies (X2) and Reading Comprehension (Y) for 0.028. Sig. Value 0.797 was higher than Alpha value 0.05 (0.797 >0,2146), Ho was accepted and Ha was rejected. In other words, there was no a positive correlation between Students’ Learning Strategies (X2) and Reading Comprehension(Y). It can be stated that Students Learning Strategies (X) simultaneously have no significant correlated the reading comprehension(Y).